Pneumothorax after insertion of central venous catheters in the intensive care unit: association with month of year and week of month. Issue 4 (12th August 2007) - Ayas, Najib T; Norena, Monica; Wong, Hubert; Chittock, Dean; Dodek, Peter M
Abstract : Rationale: One of the complications associated with insertion of central venous catheters (CVCs) is pneumothorax (PTX). Because of housestaff inexperience, it was hypothesised that rates of PTX after insertion of CVCs in teaching hospitals would be highest in July and August and in the first week of the month (beginning of intensive care unit (ICU) rotation). Methods: In a retrospective analysis of data from patients admitted to the ICU in two tertiary care teaching hospitals in British Columbia from 1999 to 2005, rates of PTX occurring after insertion of CVCs were calculated, and it was evaluated whether rates were increased during certain times of the year/month. Results: During this period, 3548 patients were admitted to these ICUs and had at least one CVC placed. 5816 CVCs were inserted; 113 PTX occurred within 2 days after insertions (1.9% per CVC). The rate during the last week of the month was greater (2.7%) than during the first, second or third weeks (1.7%, 1.8% and 1.4%, respectively). This effect persisted after controlling for the Acute Physiology and Chronic Health Evaluation II score, the number of catheters placed per patient, gender, age and hospital. Rates of PTX after catheter placement did not vary by the month of the year. Conclusions: The rate of PTX after insertion of CVCs is greatest in the last week of the month. If this effect can be verified in other centres, increased supervision of residents at the end of ICU rotations when placing CVCs should be considered. Whether this effect applies to other patient safety outcomes in the ICU also needs further study.